Creating a Shared Reality with Robots: How Augmented Reality can Facilitate Perception-Related Tasks, Guide Manipulation Behaviors, and Identify Trajectory Failures - Cleaver, Andre. (Tufts University. Tisch Library., 2024)
Thesis (Ph.D.)--Tufts University, 2024.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Jivko Sinapov.; Committee: Elaine Short, Jason Rife, and Aldis Sipolins.; Keyword: Robotics.